1H, 13C and 15N NMR assignments of two plant protease inhibitors (IRD7 and IRD12) from the plant capsicum annuum. - Gartia, J.; Barnwal, R.P.; Anangi, R.; Giri, A.R.; King, G.; Chary, K.V.R. (Biomolecular NMR Assignments, 2018)
Helicoverpa species are polyphagous pests, with the larval stages causing major damage to economically valuable crops such as cotton, tomato, corn, sorghum, peas, sunflower, wheat and other pulses. Over the years, Helicoverpa armigera has developed resistance to most classes of chemical insecticides, and consequently it is now largely controlled on cotton plants via the use of Bt transgenic crops that express insecticidal Cry toxins which in-turn expedited resistance development in a number of pest species including H. armigera. In a hope to provide other eco-friendly alternatives solutions to counter the effect of the pest, people have identified a number of protease inhibitors (PIs) from the domesticated capsicum species Capsicum annuum, several of which potently inhibited H. armigera gut proteases and impeded growth of H. armigera larva. With a view to explore and enhance the specific nature or properties of these PIs on the mechanism of inhibition, structural and functional characterization of these PIs are inevitable. Towards this goal, we have carried out complete 1H, 13C and 15N resonance assignments of two of these PIs, identified as IRD7 and IRD12, using a suite of 2D and 3D multi-dimensional and multi-nuclear NMR experiments.
Keywords: Bt transgenic; Hetero-nuclear NMR; inhibitory repeating domains; Protease inhibitors (PIs); Resonance assignments

NMR structure and dynamics of inhibitory repeat domain variant 12, a plant protease inhibitor from Capsicum annuum, and its structural relationship to other plant protease inhibitors - Gartia, Janeka; Anangi, Raveendra; Joshi, Rakesh S.; Giri, Ashok P.; King, Glenn F.; Barnwal, Ravi P.; Chary, Kandala V. R. (Journal of Biomolecular Structure & Dynamics, 2019)
Although several plant protease inhibitors have been structurally characterized using X-ray crystallography, very few have been studied using NMR techniques. Here, we report an NMR study of the solution structure and dynamics of an inhibitory repeat domain (IRD) variant 12 from the wound-inducible Pin-II type proteinase inhibitor from Capsicum annuum. IRD variant 12 (IRD12) showed strong anti-metabolic activity against the Lepidopteran insect pest, Helicoverpa armigera. The NMR-derived three-dimensional structure of IRD12 reveals a three-stranded anti-parallel beta-sheet rigidly held together by four disulfide bridges and shows structural homology with known IRDs. It is interesting to note that the IRD12 structure containing similar to 75% unstructured part still shows substantial amount of rigidity of N-H bond vectors with respect to its molecular motion. Communicated by Ramaswamy H. Sarma
Keywords: Bt transgenic; Capsicum annuum; Helicoverpa armigera; inhibitory repeating domains; NMR structure; Protease inhibitors (PIs)